2020
DOI: 10.1177/0300060520957820
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the clinical features of pericentric inversion of chromosome 9

Abstract: Objective The pericentric inversion of chromosome 9 (inv9) is one of the most common structural balanced chromosomal variations, and it is considered to be a normal population variant. The aim of this study was to re-evaluate the clinical impact of patients with inv9. Methods We studied the karyotypes from 4853 patients at a single center and retrospectively reviewed their clinical data. Results There were 67 inv9 patients among 2988 adults, and 62 of them showed different clinical features, including male and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…We identified 12 additional studies while reviewing citations of the initial studies. We categorized the 24 studies into four groups: (1) studies comparing the prevalence of Inv(9) in individuals with infertility or RPL to controls, (N = 7) [7][8][9][10][11][12][13], (2) studies reporting the prevalence of Inv(9) in individuals with infertility or RPL, no control group (N = 12) [14-25], (3) studies comparing the prevalence of infertility or RPL in individuals with Inv(9) to controls (N= 1) [26], and (4) studies reporting the prevalence of infertility or RPL in individuals with Inv(9), no controls (N = 4) [27][28][29][30] (Table 1).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 12 additional studies while reviewing citations of the initial studies. We categorized the 24 studies into four groups: (1) studies comparing the prevalence of Inv(9) in individuals with infertility or RPL to controls, (N = 7) [7][8][9][10][11][12][13], (2) studies reporting the prevalence of Inv(9) in individuals with infertility or RPL, no control group (N = 12) [14-25], (3) studies comparing the prevalence of infertility or RPL in individuals with Inv(9) to controls (N= 1) [26], and (4) studies reporting the prevalence of infertility or RPL in individuals with Inv(9), no controls (N = 4) [27][28][29][30] (Table 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In our review, the prevalence of Inv(9) in individuals with infertility or RPL ranged from 0.01 to 3.7% with most estimates between 0.5 and 2.5% (Table 1). Of the seven studies that compared this prevalence to controls without infertility or RPL, three reported a higher rate of Inv(9) in individuals with infertility [7,9,13] and four did not find a difference [8,[10][11][12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…20 A study of 2988 adult patients, 67 inv (9) cases were found and among them only 5 did not show any clinical feature and the remaining 62 adult exhibited different clinical features include infertility, azoospermia, bad obstetric history ang spontaneous abortion. 21 Although most expert considered this kind of inversion as normal variable, there still possibilities they carry another clinical problem especially in reproductive. The history of patient's childhood is not clear, so we did not know exactly whether there was alteration of genital development, micropenis or obesity in childhood but the in the initial examination, patient considered puberty was normal and there was no history of mumps and orchitis.…”
Section: Hyperprolactin 3 Obesity 4 Genetic Disordersmentioning
confidence: 99%